1999
DOI: 10.1093/clinchem/45.6.800
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Automated Chemiluminometric Assay for Measuring Free Human Glandular Kallikrein-2

Abstract: Background: Human glandular kallikrein (hK2) is a serine protease that has 79% amino acid identity with prostate-specific antigen (PSA). Both free hK2 and hK2 complexed to α1-antichymotrypsin (ACT) are present in the blood in low concentrations. We wished to measure hK2 in serum with limited contribution from hK2-ACT for the results. Methods: We developed an automated assay for hK2 with use of a select pair of monoclonal antibodies. The prototype assay was implemented on a Beckman Coulter ACCESS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 26 publications
1
9
0
2
Order By: Relevance
“…So far, no commercially available hK2 assays exist and there is not universally accepted calibrator for hK2 like there is for PSA. There have been three hK2 assays available to date: (i) the assay in the present study; 34 (ii) the Beckman Coulter total hK2 assay; 40 and (iii) the Turku hK2 assay. 41 The hK2 assay used in this study measured about 1.5-fold higher concentrations when compared with the Beckman Coulter hK2 research assay (obtained on 29 samples, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…So far, no commercially available hK2 assays exist and there is not universally accepted calibrator for hK2 like there is for PSA. There have been three hK2 assays available to date: (i) the assay in the present study; 34 (ii) the Beckman Coulter total hK2 assay; 40 and (iii) the Turku hK2 assay. 41 The hK2 assay used in this study measured about 1.5-fold higher concentrations when compared with the Beckman Coulter hK2 research assay (obtained on 29 samples, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…While the total PSA level alone is neither sensitive nor specific enough for the early diagnosis of prostate cancer, the ratio of free to total PSA may improve both sensitivity and specificity [32]. The application of hK2 as an additional serum marker for the detection, prognosis, and monitoring of prostate cancer patients has recently emerged [33][34][35][36][37]. The measurement of both kallikreins introduces the possibility of multiple parameter testing for prostate cancer.…”
Section: Psa As An Oncologic Markermentioning
confidence: 99%
“…There are no commercially available hK2 assays, and there is no universally accepted calibrator for hK2 as there is for PSA. Three hK2 assays have been used for most hK2 testing to date: the assay in the present study [31]; the Beckman Coulter total hK2 assay [35]; and the Turku hK2 assay [36]. The present assay measured about 1.5 times higher hK2 concentrations than the Beckman Coulter assay.…”
Section: Discussionmentioning
confidence: 99%